Exploring EFL Classroom Interaction: An Analysis of Teacher Talk at Senior High School Level - Ardesia Winanta; Dewi Rochsantiningsih; Slamet Supriyadi (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
The study on teacher talk has been considered as a crucial aspect in EFL classroom interactions due to it assists teachers to build interactive teaching-learning activities. The present study attempts to scrutinize talk types of an in-service teacher in an EFL classroom interaction based on the Foreign Language Interaction (FLINT) system proposed by Moskowitz (1971). It was conducted qualitatively through the lens of a case study by involving an experienced female EFL teacher at a senior high school level. The data were collected through several procedures consist of direct observation, audio recording, and interview section. The result disclosed that from 12 talk types in the FLINT system, 9 types were used by the teacher. One of them ‘praises or encourages’ took place as the highest type. It denoted that the teacher really appreciated the students’ effort to boost their learning motivation. Meanwhile, the least type used by the teacher was ‘criticizes student behavior’. According to the interview result, the teacher rarely used criticism because she tried to keep the students' feelings and mental. Thus, this study is expected to provide a new reference especially for EFL teachers as a consideration in using talk to get students’ attention and participation during the learning process.